COMPARATIVE ANALYSIS OF THE PROFITS OF FATTENING SUPER BREED CAWS WITH MADRAS BREEDS IN SIMALUNGUN DISTRICT, NORTH SUMATRA - Haryani Sinaga; Fadli; Zuriani (CV. Radja Publika, 2022)
Simalungun Regency is the 4th highest beef producing district in North Sumatra thus making Simalungun Regency very potential in fattening cattle. This study aims to determine the difference between the advantages of fattening cattle using super sheeds and madras sheeds in Simalungun Regency, North Sumatra. The data analysis method used is descriptive quantitative with statistical analysis tools independent sample t-test. The results showed that the profits of the super breeders of cattle fattening business were not the same as the Madras breeds with the average profit per kg obtained by super breeders of cattle fattening of Rp. 466/kg, while the average profit per kg obtained by Madras cattle fattening breeders is Rp. 1,391/kg. This result can be strengthened by the value of t arithmetic (17.011) > t table (2.048) and p value (0.000) < α (0.025), so it can be concluded that the profit of fattening cattle on super breeds is not the same as that of madras seedlings.